(untitled) (Scientific journal of the Fergana State University, 2023)
From the end of the 1920s. the repressive policy of the Soviet government intensified. As a result, the national intelligentsia and enlighteners of Turkestan were investigated under various nationalist pretexts. The article analyzes the life, pedagogical activity, creativity, spiritual heritage and fate of the young victim of such a Stalinist policy of repression, the talented poet of Uzbek literature of the early twentieth century, Osman Nasyr. In Soviet times, his work was distorted, using it as an instrument of ideological propaganda. During the years of independence, the poet’s work acquired its true essence.